Prolactin and Autoimmunity - Borba, Vânia Vieira; Zandman-Goddard, Gisele; Shoenfeld, Yehuda (Frontiers in Immunology, 2018)
The great asymmetry of autoimmune diseases between genders represents one of the most enigmatic observations among the mosaic of autoimmunity. Sex hormones, are believed to play a crucial role on this dimorphism. The higher prevalence of autoimmunity among women at child-bearing ages, disease onset/relapses during pregnancy and post-partum are some of the arguments that support this hypothesis. Certainly, motherhood represents one of the most remarkable challenges for the immune system, which not only has to allow for the conceptus, but also deal with complex endocrine alterations. Hormonal homeostasis is known to exert a crucial influence in achieving a competent and healthy immune system. Prolactin has a bioactive function acting as a hormone and a cytokine. It interferes with immune system modulation, mainly inhibiting the negative selection of autoreactive B lymphocytes. Likewise, hyperprolactinemia has been described in relation to the pathogenesis and activity of several autoimmune disorders. Dopamine is an effective inhibitor of prolactin secretion due either a direct influence on the hypophysis or stimulation of postsynaptic dopamine receptors in the hypothalamus, arousing the release of the prolactin inhibitory factor. Hence, dopamine agonists have proven to offer clinical benefits among autoimmune patients and represents a promising therapy to be explored. In this review, we attempt to provide a critical overview of the link between prolactin, autoimmune diseases and motherhood.